Revision of the genus Hannia (Teleostei, Terapontidae), with description of a new species, Hannia wintoni, from the Kimberley, Western Australia - Shelley, James J.; Delaval, Aurélien; Le Feuvre, Matthew C.; Dempster, Tim; Raadik, Tarmo A.; Swearer, Stephen E. (Zootaxa, 2020)
The systematics of the genus Hannia Vari 1978, endemic to freshwater habitats of remote north-western Australia, is revised in light of recent collections in the region and a molecular study of the group that identified an undescribed candidate species. A new freshwater fish species (Hannia wintoni sp. nov) is described based on analysis of multiple nuclear genetic markers (53 allozyme loci), mitochondrial DNA sequence data (601 bp cytochrome b) and morphology (examination of a suite of 66 morphometric and meristic characters). Head profile, postorbital length, maximum length, preopercular spines and pectoral-fin rays are characters that best distinguish H. wintoni sp. nov from its only congener, H. greewayi. While the existing description of H. greenwayi is robust and accurate, we present a number of additional characters that enhance to the original description, based on type and fresh material. Information on the known distribution, habitats and conservation status of the two species is summarised. The new species is a narrow-range endemic.